2016
DOI: 10.21037/jovs.2016.05.05
|View full text |Cite
|
Sign up to set email alerts
|

Subxiphoid mediastinal lymphadenectomy

Abstract: Video-assisted thoracoscopic surgery (VATS) has experience an exponential growth in lung anatomic resections. Since its beginnings in early 90s with the conventional multiport VATS to the more recent uniportal approach, a continuous search for a less invasive procedure has fueled the development of minimally invasive thoracic surgery. In this sense, subxiphoid uniportal VATS has surge as a uniportal option that avoids damage to the intercostal nerve created in a transthoracic approach. In order for this techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Exclusion criteria for using the uniportal subcostal approach were chest wall tumor involvement, central masses, previous thoracic surgery, adhesion, body mass index BMI>30 kg/m 2 [3, 6, 7], cardiomegaly, cardiac comorbidities due to compression on the heart specially on the left side, and enlarged lymph nodes with confirmed N1 or N2 disease [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exclusion criteria for using the uniportal subcostal approach were chest wall tumor involvement, central masses, previous thoracic surgery, adhesion, body mass index BMI>30 kg/m 2 [3, 6, 7], cardiomegaly, cardiac comorbidities due to compression on the heart specially on the left side, and enlarged lymph nodes with confirmed N1 or N2 disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that patients with obesity are not good candidate for subcostal approach [7]; therefore the challenging point also in obese patients is high location of the diagram, because of the abdominal pressure effect; therefore we compromise that, by resection both xiphoid process, mediastinal and pericardial fatty tissue, these steps allow enlarging the space for instruments manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The view is caudal-cranial and anterior to posterior, so the access for the view of the posterior mediastinum is difficult, resulting in the need for the lung requiring more traction to assess the lesions in this area. The complete dissection of the subcarinal lymph nodes is more difficult to accomplish than transthoracic approach, especially on the left side (13). When a bleeding is difficult to control by this approach, an extension of the subxiphoid incision is unlikely to be useful so an additional thoracic port must be performed (3-4 cm utility incision).…”
Section: Discussionmentioning
confidence: 99%
“…However, the longer distance from the subxiphoid or subcostal incision to the hilum makes this approach more difficult to perform major pulmonary resections. Nevertheless, in expert hands this technique allows the possibility to perform complex resections (6), lymph node dissection (7) and anatomic segmentectomies (8).…”
Section: Introductionmentioning
confidence: 99%